2013
DOI: 10.1117/1.jbo.18.1.015003
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse light reflectance signals as potential indicators of loss of viability in brain tissue due to hypoxia: charge-coupled-device-based imaging and fiber-based measurement

Abstract: Abstract. Brain tissue is highly vulnerable to ischemia/hypoxia, and real-time monitoring of its viability is important. By fiber-based measurements for rat brain, we previously observed a unique triphasic reflectance change (TRC) after a certain period of time after hypoxia. After TRC, rats could not be rescued, suggesting that TRC can be used as an indicator of loss of brain tissue viability. In this study, we investigated this diffuse-reflectance change due to hypoxia in three parts. First, we developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…4e). In our previous study, an increase in the NIR diffuse reflectance, i.e., an increase in the light scattering, was shown to be associated with the irreversible cell damage after hypoxia 8 . Thus, the reflectance increase within the region with reduced blood flow in Fig.…”
Section: Pixels Of Area With Increased Nir Reflectancementioning
confidence: 99%
See 1 more Smart Citation
“…4e). In our previous study, an increase in the NIR diffuse reflectance, i.e., an increase in the light scattering, was shown to be associated with the irreversible cell damage after hypoxia 8 . Thus, the reflectance increase within the region with reduced blood flow in Fig.…”
Section: Pixels Of Area With Increased Nir Reflectancementioning
confidence: 99%
“…In the nearinfrared (NIR) spectral region, the reduced scattering coefficient of the gray matter is two orders of magnitude larger than the absorption coefficient 7 , and the use of light scattering signal therefore enables sensitive monitoring of the events associated with spreading depolarization, as well as irreversible cell damage. We previously observed an occurrence of AD by NIR diffuse reflectance measurement in the rat global hypoxic brain model 8 . In that study, we found that AD was able to be detected as a wave-like reflectance change and the irreversible light-scattering increase after the AD was associated with irreversible cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results are an average of signals from different head tissue layers (partial volume effect), which may impact hemodynamics imaging. In future studies, simultaneous imaging and diffuse reflectance based source-detector fiber optics configuration [57] is highly recommended to validate drugs' effects on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse reflectance spectroscopy (DRS) is one of most promising technique for evaluating optical properties of in vivo brain tissue. Several imaging techniques based on the diffuse optical spectroscopy have been used to investigate the cortical hemodynamics [3][4][5] and tissue viability 6 .…”
Section: Introductionmentioning
confidence: 99%